2013
DOI: 10.1371/journal.pone.0063391
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Mass, and Glucose-Uptake Activity of 18F-FDG-Detected Brown Adipose Tissue in Humans Living in a Temperate Zone of Italy

Abstract: BackgroundThe 18F-fluorodeoxyglucose (18F-FDG)-detected brown adipose tissue (BAT), is enhanced by cold stimulus and modulated by other factors that still have to be disentangled. We investigated the prevalence, mass, and glucose-uptake activity of 18F-FDG-detected BAT in a population of adults living in the temperate climatic zone of the Rome area.Methods and FindingsWe retrospectively analyzed 6454 patients who underwent 18F-FDG positron emission tomography/computed tomography (PET/CT) examinations. We found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
73
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(80 citation statements)
references
References 37 publications
7
73
0
Order By: Relevance
“…6,[13][14][15][16][17]19,21 BAT activity was found to be higher in women, in many oncology studies. [13][14][15][16][17]20 However, no sex differences were found in 18 FDG-PET∕CT studies with cold exposure. 6,22 The oncology studies had very large sample sizes but did not include cold exposure, whereas the studies using 18 FDG-PET∕CT with cold exposure had relatively small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…6,[13][14][15][16][17]19,21 BAT activity was found to be higher in women, in many oncology studies. [13][14][15][16][17]20 However, no sex differences were found in 18 FDG-PET∕CT studies with cold exposure. 6,22 The oncology studies had very large sample sizes but did not include cold exposure, whereas the studies using 18 FDG-PET∕CT with cold exposure had relatively small sample sizes.…”
Section: Discussionmentioning
confidence: 99%
“…We showed that body fatness parameters were negatively correlated with BAT-d, which is consistent with the results of various studies that used 18 FDG-PET∕CT, regardless of the presence of cold exposure. 6,[14][15][16][17]19,20 Although we should consider the possibility that the BAT-d was affected by subcutaneous fat thickness, 26 the subcutaneous fat thickness in the supraclavicular region is within a very narrow range and has little effect on the measured parameters. For instance, the fat thickness in the supraclavicular region ranged from 0.6 to 2.5 mm when evaluated by B-mode ultrasonography in this study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The detectability of BAT by [ 18 F]fluorodeoxyglucose-PET-CT imaging at room temperature follows a circannual cycle, both in the northern and southern hemispheres (31)(32)(33), with low detectability of BAT in summer (i.e., short day) compared with winter (i.e., long day). Although differences in outside temperature over the year would be a likely explanation for this phenomenon, the detectability of BAT showed a stronger correlation with day length than with outside temperature (31).…”
Section: Discussionmentioning
confidence: 99%